2019
DOI: 10.3390/medicina55110746
|View full text |Cite
|
Sign up to set email alerts
|

A Consecutive 25-Week Program of Gait Training, Using the Alternating Hybrid Assistive Limb (HAL®) Robot and Conventional Training, and its Effects on the Walking Ability of a Patient with Chronic Thoracic Spinal Cord Injury: A Single Case Reversal Design

Abstract: Background and Objectives: In this study, we examined the effect of a consecutive 25-week gait training program, consisting of 5-week alternating phases of Hybrid Assistive Limb (HAL)-assisted robot gait training and conventional gait training, on the walking ability of a 50-year-old man with a chronic thoracic spinal cord injury (SCI). Materials and Methods: Clinical features of this patient’s paraplegia were as follows: neurological level, T7; American Spinal Cord Injury Association Impairment Scale Score, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Our data supports findings of previous studies reporting of improvements in terms of spatiotemporal gait parameters and joint angles during the gait cycle after HAL R treatment (Kanazawa et al, 2019;Watanabe et al, 2019). However, presented data only shows statistical significance and not necessarily clinical significance as no comparison was made with minimal clinically important difference values for this population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data supports findings of previous studies reporting of improvements in terms of spatiotemporal gait parameters and joint angles during the gait cycle after HAL R treatment (Kanazawa et al, 2019;Watanabe et al, 2019). However, presented data only shows statistical significance and not necessarily clinical significance as no comparison was made with minimal clinically important difference values for this population.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently studies should not only focus on functional outcomes but also on physiology when assessing the rehabilitation progress. Hence, several studies evaluated gait parameter changes after HAL R treatment and found improvements, for example in patients after Stroke (Tanaka et al, 2019), in groups of patients with cerebral palsy (Matsuda et al, 2018;Mataki et al, 2020) and in case reports of patients with SCI (Kanazawa et al, 2019;Watanabe et al, 2019). Investigations in larger groups of people living with SCI are missing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, gait training using the Alternating Hybrid Assistive Limb (HAL R ) Robot was reported. By combining gait training using HAL-assisted and conventional gait training with physical therapy, the ability of patients with a chronic SCI to walk may be improved over a short period (Sczesny-Kaiser et al, 2015;Shimizu et al, 2017;Matsuda et al, 2018;Kanazawa et al, 2019). The potential for gait training using HAL to improve the ability of patients with chronic severe incomplete tetraplegic SCI to walk was also shown.…”
Section: Rehabilitation Approaches For Chronic Spinal Cord Injurymentioning
confidence: 99%